2002
DOI: 10.4314/sajas.v32i3.3744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various dietary n-3 / n-6 fatty acid ratios on the performance and body composition of broilers

Abstract: Different combinations of saturated and unsaturated fatty acids were fed to broilers to establish their effect on the fatty acid composition of the broiler carcass and the abdominal fat pad. Six combinations of Canola acid oil (CAO, high levels of C18:3n-3 and monounsaturated fatty acids) and Famarol acid oil (FAO, high levels of C18:2n-6 and saturated fatty acids) were included in the broiler diets from one day of age to six weeks of age, viz. 100% FAO, 80% FAO-20% CAO, 60% FAO-40% CAO, 40% FAO-60% CAO, 20% F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…Conversion of ALA (18:3n-3) to EPA (20:5n-3) involves sequential ∆6-desaturation, chain elongation, and ∆5-desaturation. EPA is, in turn, converted to DPA (Olomu and Baracos 1991;Lopez-Ferrer et al 1999;Coetzee and Hoffman 2003). As several reports (Haug et al 2007;Ponte et al 2008;Qi et al 2010), our study (Table 7) showed that reducing dietary 18:2n-6/18:3n-3 ratio linearly increased the enrichment of EPA and DPA, which implied that dietary n-3 PUFAs gave rise to higher tissue levels of EPA and DPA in a dosage-dependent manner.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Conversion of ALA (18:3n-3) to EPA (20:5n-3) involves sequential ∆6-desaturation, chain elongation, and ∆5-desaturation. EPA is, in turn, converted to DPA (Olomu and Baracos 1991;Lopez-Ferrer et al 1999;Coetzee and Hoffman 2003). As several reports (Haug et al 2007;Ponte et al 2008;Qi et al 2010), our study (Table 7) showed that reducing dietary 18:2n-6/18:3n-3 ratio linearly increased the enrichment of EPA and DPA, which implied that dietary n-3 PUFAs gave rise to higher tissue levels of EPA and DPA in a dosage-dependent manner.…”
Section: Discussionsupporting
confidence: 72%
“…In this study, the ARA (20:4n-6) levels of treatments containing corn oil with different proportions (CO, CL1, and CL2, enriching with LNA) were higher than that of LO group in breast muscle, but the ARA (20:4n-6) levels were similar among CO, CL1, and CL2 groups, which suggested that dietary LNA (18:2n-3) could increase ARA deposition in meat in a dosage-independent manner. LO group had the lowest ARA (20:4n-6), which also reflected that high amounts of ALA (18:3n-3) could decrease the conversion of LNA (18:2n-6) to ARA (20:4n-6) (Coetzee and Hoffman 2003;He et al 2009). …”
Section: Discussionmentioning
confidence: 84%
“…It has been recorded that chickens could modify their lipid profile within a week after replacement of the dietary lipid source (Lopez-Ferrer et al, 2000). There is, therefore, considerable potential for the manipulation of the fatty acid profiles of poultry tissue by dietary means, thus to increase the supply of omega-3 (n-3) polyunsaturated fatty acids (PUFA) suitable for human consumption (Coetzee & Hoffman, 2002). Researchers illustrated that by feeding the relevant dietary unsaturated fatty acids, both polyunsaturated/saturated (PUFA/SFA) ratio (Warnants et al, 1998) and omega-6/omega-3 (n-6/n-3) ratios (Wood et al, 1999) of animal adipose tissue could be altered to fall within the dietary guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Eggs and poultry meat rich in omega-3 fatty acids can be produced by using feed ingredients rich in omega-3 fatty acids. In general, studies have been conducted to determine the effects of different omega-3 fatty acids sources in diets on the cholesterol and fatty acid composition of egg yolk and South African Journal of Animal Science 2003, 33 (4) 267 © South African Society for Animal Science meat (Caston & Leeson, 1990;Cherian & Sim, 1991;Hammershøj, 1997;Coetzee & Hoffman, 2002;Komprda et al, 2003). However, studies with regard to the effects of omega-3 fatty acids on blood cholesterol are lacking.…”
Section: Introductionmentioning
confidence: 99%